INSTAGRAM SEBAGAI MEDIA PUBLIKASI HUMAS (STUDI PADA AKUN @BANK_INDONESIA_BENGKULU) - Lestari, Salsabila Dwistika; Alfarabi, Alfarabi; Yuliati, Yuliati (MEDIOVA: Journal of Islamic Media Studies, 2023)
This study aims to find out how Instagram @bank_indonesia_benngkulu as a new media is used as a publication medium by public relations practitioners at the Bank Indonesia Representative Office in Bengkulu Province. The research method used in this study is a qualitative method with a descriptive approach, using data collection methods by interview and observation. The result of this research is that the public relations of the Bank Indonesia Representative Office in Bengkulu Province has carried out its role as a communication facilitator and communication technician. Public Relations has used Instagram as one of the media in the publication and dissemination of information that has been designed. The ability to write public relations is very necessary in conveying messages to the public. Writing text descriptions/captions has shown 5W + 1H elements (what, who, when, where, why, how) where the content presented contains information with several forms of journalistic documentation in the form of photography, videography, posters/flyers, and comics as a narrative medium. . Utilization of Instagram features is very helpful in publishing and disseminating information, coupled with attractive content packaging and message descriptions, making it easy for people to understand and understand the information presented.